GORD in adults - Delaney, Brendan (BMJ Publishing Group, 2008)
INTRODUCTION: Up to 25% of people have symptoms of gastro-oesophageal reflux disease (GORD), but only 25-40% of these have oesophagitis visible on endoscopy. About 80% of people with GORD will have recurrent symptoms if treatment is stopped, and severe oesophagitis may result in oesophageal stricture or Barrett's oesophagus. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical questions: What are the effects of initial treatment of GORD associated with oesophagitis? What are the effects of maintenance treatment of GORD associated with oesophagitis? We searched: Medline, Embase, The Cochrane Library, and other important databases up to July 2007 (BMJ Clinical Evidence reviews are updated periodically; please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations, such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 29 systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review, we present information relating to the effectiveness and safety of the following interventions: antacids/alginates, H(2) receptor antagonists, laparoscopic surgery, lifestyle advice/modification, motility stimulants, open surgery, and proton pump inhibitors.